The Influence of Brand Image on Purchasing Decision of Le Minerale Bottled Water among Adolescents in Surakarta: A Psychological Perspective - Mashlihah, Yunda Hidayati; Hapsari, Maharani Tyas Budi (Manunggal Halim Jaya, 2025)
This study aims to determine how much influence the brand image instilled by AMDK-branded Le Minerale has on purchasing decisions among teenagers in Surakarta City. This study uses a quantitative survey approach via Google with a purposive sampling technique. This study was conducted on teenagers in Surakarta City aged 20-29 years, who are potential and actual consumers of the AMDK brand Le Minerale, with a sample of 112 respondents consisting of 43 men and 69 women using the Joseph Hair formula. The data analysis techniques used are validity testing, reliability testing, normality testing, simple linear regression analysis, and hypothesis testing. The data was processed with the help of the IBM SPSS statistical application version 27.0. Based on the results of the t-test, the t-count value was obtained as 3.698 with a significance value of 0.000 less than 0.05 (0.000 <0.05), indicating that the initial hypothesis was accepted. The results of the simple linear regression equation show Y = 35.304 + 329X, meaning that the direction of the influence is positive or in the same direction. If the brand image variable (X) increases by 1, then the purchasing decision variable (Y) also increases by 0.329 plus a constant, and vice versa. This confirms the significant and positive influence of brand image on the purchasing decision of Le Minerale branded AMDK on teenagers in Surakarta City. Based on these findings, it can be concluded that 11.1% of purchasing decisions are influenced by brand image. This theory uses consumer psychology to understand how brand image influences the purchasing decision process in teenagers, with psychological aspects such as perception, motivation, learning, and emotions playing an important role in the study.